Views on COVID-19 vaccination of young children in Ireland, results from a cross-sectional survey of parents. Issue 39 (16th September 2022) - Marron, Louise; Ferenczi, Annamaria; O'Brien, Katie M.; Cotter, Suzanne; Jessop, Lucy; Morrissey, Yvonne; Migone, Chantal
Highlights: In Ireland over 50 % of parents intend to vaccinate their child aged 0–48 months. Belief that COVID-19 is a serious illness is associated with intention to vaccinate. Of those who do not intend to vaccinate, the primary concern is vaccine safety. Vaccine information and communication should be tailored to parents' needs. Vaccine communication should focus on vaccine safety in children. Abstract: Vaccination of children aged 5 years and older is recommended as part of a multifaceted strategy to protect children against SARS CoV-2 infection and serious disease, and to control the spread of infection. COVID-19 vaccine trials in children aged less than5 years are underway, however, parental acceptance of vaccines for this age group is unknown. Between June and August 2021, a cross-sectional national survey of parental attitudes towards childhood vaccination in Ireland was conducted. Parents of children aged 0–48 months were surveyed to determine their attitudes towards COVID-19 vaccines for their children. A total of 855 parents were surveyed. Overall, 50.6 % reported that they intend to vaccinate their child, 28.7 % reported that they did not intend to vaccinate and 20.2 % were unsure. Among those who stated that they did not intend to vaccinate their child, concern about risks and side effects of vaccination was the primary reason reported (45.6 %). The most frequently reported information needs related to side effects of the vaccine (64.7 %) and vaccine safety (60.3 %). Results of the multivariable analysis showed that believing COVID-19 can be a serious illness in children was a strong predictor of parental intention to vaccinate (aOR 4.88, 95 % CI 2.68, 8.91, p-value < 0.001). In comparison with Irish-born parents, parents born in a Central and Eastern European country were less likely to report intention to vaccinate (aOR 0.21, 95 % CI 0.09, 0.47, p-value, <0.001). Parental belief in vaccine importance and safety and parental trust in official vaccine information sources were associated with increased parental intention to vaccinate. Understanding parental attitudes to vaccination of young children against COVID-19 is important to tailor the provision of information to parents' needs, and to inform the development of vaccination information and communication campaigns for current and future COVID-19 immunisations programmes for children.